N.S. LESKOV'S VIEWS TO A NAME (ONOMASTIC COMMENTARY) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-83-94The article deals with the N.S. Leskov's views to a proper name in Russian culture. The writer highly values the Russian name as part of the national cultural fund. In N.S. Leskov's opinion, the wide use of native Russian names in naming will significantly enrich our culture. The article analyzes the anthroponyms of N.S. Leskov’s essay “Satiety with nobility” (1888), dedicated to the loss of the tradition of calling by name in Russian speech culture. The writer creatively comprehends the potential of proper name, thereby forming a unique metatextual reality of his works. The proper name plays an important role in N.S. Leskov’s creative workshop.Key words: name, onomastics, biblical names, autobiographical names, “Satiety of nobility” (1888), N.S. Leskov